THINGS FROM THE FUTURE How can we crowdsource innovation foresight with games? - Lepistö, Vesa (My University, 2017)
In the current world uncertainty is more dominant than it used to be. One of the key forces for constant change is innovation. Innovations can be radical and create surprising effects. Can there be ways of anticipating these unforeseen effects of innovation? Or can the course of future innovations be managed somehow? Innovation foresight processes are required to communicate between different stakeholders on an extensive scale to be able to build comprehensive and understandable future options. Knowledge on future and innovation is no more the exclusive right of experts. This study tries to find new ways of engaging people with the innovation foresight work as well as get new audiences to participate in it. Games and crowdsourcing are two possible solutions to this. Theories covering innovation, foreisght and crowdsourcing are plentiful but scattered, and do not form a coherent framework for innovation foresight. Study is approaching the research topic from two perspectives: what kind of innovation foresight knowledge can we create with games, and what innovation foresight activities can we crowdsource with games? For these targets study has used two different methods, an innovation game case study experiment and a questionnaire targeted to Finnish innovation experts. Game case study consisted of a foresight analysis of 310 ”future thing” ideas generated with an innovation card game. The results revealed that games can enhance the creativity of the players and generate many unexpected uses of future technologies and services. Ideas were also rich with future hopes and fears and they had multidimensional content including different PESTE-variables. Questionnaire was targeted to map views related to the usability of games in different phases of the innovation foresight process. According to responses gaming can be used to observe weak signals, to form wild cards, perceive hopes and fears, and to develop new visions for the future. But games are not seen as suitable for decision-making nor forecasting future trends. Crowdsourcing can enhance the ”crowd wisdom” of the foresight process. Crowd wisdom means that groups are often smarter than the smartest people in them. This phenomenon is based on the thought that “no one knows everything, but everyone knows something”. The challenge in crowdsourcing is to motivate people to participate and engage. Games can be a powerful solution to innovation foresight motivation challenge, and they may also generate different solutions than other methods. But games cannot replace the foresight process. To subject foresight to games and gamification would take too many resources, be expensive, difficult to manage, and results would be risky. Crowdsourcing innovation foresight can often be carried out more effectively when using existing social media platforms such as Facebook, Twitter etc. instead of games. In any case, crowd wisdom is too valuable resource not to be exploited in foresight.